2002
DOI: 10.1515/gmj.2002.13
|View full text |Cite
|
Sign up to set email alerts
|

Existence and Properties of ℎ-Sets

Abstract: In this note we shall consider the following problem: which conditions should satisfy a function ℎ : (0, 1) → ℝ in order to guarantee the existence of a (regular) measure μ in with compact support and for some positive constants 𝑐2, and 𝑐2 independent of γ ∈ Γ and 𝑟 ∈ (0,1)? The theory of self-similar fractals provides outstanding examples of sets fulfilling (♡) with ℎ(𝑟) = 𝑟𝑑, 0 ≤ 𝑑 ≤ 𝑛, and a suitable measure μ. Analogously, we shall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…There it turns out that one first needs a sound knowledge about the existence and quality of the corresponding trace spaces. Returning to the first results in that respect in [Br2], see also [Br3,Br4,Br1], we found that the approach can (and should) be extended for later applications. More precisely, for a positive continuous and non-decreasing function h : (0, 1] → R (a gauge function) with lim r→0 h(r) = 0, a non-empty compact set Γ ⊂ R n is called h-set if there exists a finite Radon measure µ in R n with supp µ = Γ and µ(B(γ, r)) ∼ h(r), r ∈ (0, 1], γ ∈ Γ, see also [Ro, Chapter 2] and [Ma,p.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…There it turns out that one first needs a sound knowledge about the existence and quality of the corresponding trace spaces. Returning to the first results in that respect in [Br2], see also [Br3,Br4,Br1], we found that the approach can (and should) be extended for later applications. More precisely, for a positive continuous and non-decreasing function h : (0, 1] → R (a gauge function) with lim r→0 h(r) = 0, a non-empty compact set Γ ⊂ R n is called h-set if there exists a finite Radon measure µ in R n with supp µ = Γ and µ(B(γ, r)) ∼ h(r), r ∈ (0, 1], γ ∈ Γ, see also [Ro, Chapter 2] and [Ma,p.…”
Section: Introductionmentioning
confidence: 75%
“…60]. Here we essentially follow the presentation in [Br2,Br3,Br4,Br1], see also [Ma] for basic notions and concepts.…”
Section: H-sets γmentioning
confidence: 99%
See 1 more Smart Citation
“…Definition 3. (see [10]). Let Γ ⊂ R d be a nonempty compact set and h ∈ H. We say that Γ is an h-set if there are a constant c * 1 and a finite countably additive measure µ on R d such that supp µ = Γ and…”
Section: Introductionmentioning
confidence: 96%
“…Definition 4. (see [5]). Let Γ ⊂ R d be a nonempty compact set and h ∈ H. We say that Γ is an h-set if there are a constant c * 1 and a finite countably additive measure µ on R d such that supp µ = Γ and…”
mentioning
confidence: 96%